Medical reporting recommendations: a gap between practical and theoretical approach of journalists in Italy - Marianna Di Croce; Luisa Vercellesi; Martina Laccisaglia; Flavia Bruno (Istituto Superiore di Sanità, 2012)
OBJECTIVE: This survey involved medical reporters to identify degrees of theoretical and actual compliance to recommendations for health reporting. METHODS: The questionnaire was addressed to 450 Italian journalists and obtained a redemption of 23.1%. RESULTS: Major gaps between theoretical agreement and professional practice were: need of scientific background and continuing education; importance of avoiding sensationalism, assessment of scientific protocols and results, reporting of results as absolute risk and numbers needed to treat, attention to the conflict of interest. Two homogeneous profiles emerged. Group 1 includes journalists working in newspapers and shows a large gap between theory and practice. Group 2 includes mainly journalists working in technical medical media and shows a higher consistency between the two settings. DISCUSSION: An improvement in theoretical understanding of medical literature is advisable, but interventions are needed in the working practice in particular in newspapers, a setting where approaches are more difficult.